ABO blood group as a potential risk factor for venous thromboembolism in acutely injured patients - Muellner, Sarah K.; Haut, Elliott R.; Streiff, Michael B.; Holcomb, John B.; Cotton, Bryan A. (Thrombosis and Haemostasis, 2011)
Venous thromboembolism (VTE) is a major health problem that results in a significant burden on hospitals and patients. VTE screening and prophylaxis protocols in trauma patients vary significantly among hospitals and providers. In addition, many patients develop VTE even in the absence of “high-risk” categories. Therefore, more research is needed to better understand and prevent VTE in these patients. ABO blood group has long been recognised as a risk factor for VTE, but its contribution to VTE risk in the trauma setting is poorly studied. This paper reviews the literature describing the link between ABO blood group and VTE risk and the implications for VTE screening and prophylaxis in trauma patients. The effect of ABO blood groups are genotype-dependent – in most populations the A1 allele and the B allele increase risk while A2, O1, and O2 decrease risk of VTE. ABO group is a major determinant of plasma von Willebrand factor (vWF) and factor VIII levels, thereby (partially) mediating the effects of ABO blood group on VTE susceptibility. In addition, ABH antigens alter plasma levels of vWF via clearance mechanisms, which are in turn mediated by ADAMTS13. ABO blood group is a risk factor for VTE that warrants further investigation in trauma patients.
Keywords: Deep-vein thrombosis; hypercoagulability; pulmonary embolism; surgery; venous thrombosis